SCIENTIFIC APPROACHES TO THE FAMILY WITH CHILD PROBLEM - Mushkevich, Myroslava Ivanovna (Psychological Prospects Journal, 2013)
The article reveals the main difficulties in the functioning of a family having a problem child. The phases of parents' reactions to the birth of a problem child are identified, the range of problems that are encountered in families is generalized, their typical functioning situations and dysfunctional symptoms are described.